WinRob: A program for teaching robot mechanics and control - Tenreiro Machado, J. A. (2019)
The paper presents a program for robotics education that runs on standard IBM-PC's under the Microsoft Windows environment. The WinRob package is designed for undergraduate students and emphasis the fundamental aspects of robot modelling and control. The software is self-explanatory and uses menus, dialog boxes with figures and context-dependent on-line help. In this perspective, students are motivated to investigate on the kinematics, dynamics, trajectory planning and control in order to get insight into robotics.